2014
DOI: 10.1007/978-1-4939-0781-6_9
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Polytopes and Suzuki Simple Groups

Abstract: For each q ¤ 2 an odd power of 2, we show that the Suzuki simple group S D S z.q/ is the automorphism group of considerably more chiral polyhedra than regular polyhedra. Furthermore, we show that S cannot be the automorphism group of an abstract chiral polytope of rank greater than 4. For each almost simple group G such that S < G Ä Aut.S/, we prove that G is not the automorphism group of an abstract chiral polytope of rank greater than 3, and produce examples of chiral 3-polytopes for each such group G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Some results in this vein are known. For instance in [13], it is proved that every almost simple group G with socle Sz(q) is the automorphism group of at least one abstract chiral polyhedron. And in [20], it is shown that the only almost simple groups with socle L 2 (q) that are not automorphism groups of abstract chiral polyhedra are L 2 (q), P GL(2, q), and a group of the form L 2 (9).2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some results in this vein are known. For instance in [13], it is proved that every almost simple group G with socle Sz(q) is the automorphism group of at least one abstract chiral polyhedron. And in [20], it is shown that the only almost simple groups with socle L 2 (q) that are not automorphism groups of abstract chiral polyhedra are L 2 (q), P GL(2, q), and a group of the form L 2 (9).2.…”
Section: Discussionmentioning
confidence: 99%
“…x := (1,14,17,21,10,5,2,16,18,12,8) (3,6,19,22,15,9,20,23,4,7,11), y := (1,8,6,10,21,22,19,12,11,7,4,5,3,18,9) (2,23,20,16,13) (14,15,17), and t := xy. The pair x, t satisfies (i)-(iii) of Theorem 1.1.…”
Section: Proof Of Theorem 11 For G Sporadicmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an atlas existed already in the regular case [28]. These atlases turned out to be very inspiring to find patterns and get classification results (see [26,20,27] for instance).…”
Section: Introductionmentioning
confidence: 95%
“…In [1], Isabel Hubard and Dimitri Leemans have embarked in an extensive analysis on the abstract polytopes admitting an almost simple group with socle a Suzuki group as automorphism group. Except for an answer to [1, Conjecture 1], their analysis is very satisfactory and gives a great insight on such abstract polytopes.…”
Section: Introductionmentioning
confidence: 99%